Quantitative analysis of nuclear morphological alterations in oral mucosal epithelial cells exposed to electromagnetic radiation from mobile devices - Enni Halimatussadiyah Pakpahan; Adi Hartono (Universitas Islam Negeri Sumatera Utara, 2025)
Electromagnetic wave (EMW) radiation from mobile devices has raised public health concerns due to its potential biological effects on rapidly regenerating tissues such as the oral mucosa. This study quantitatively analyzed nuclear morphological alterations in oral mucosal epithelial cells following controlled EMW exposure. A quasi-experimental pretest–posttest control group design was conducted with 30 healthy participants aged 18–25 years, randomly assigned to control (n = 15) and treatment (n = 15) groups. The treatment group was exposed to EMW at 1800 MHz for 60 minutes per day over 14 consecutive days, using an active smartphone placed 1 cm from the right cheek during a simulated voice-call condition. The control group received no direct exposure. Buccal epithelial cells were collected via oral swab, fixed in Carnoy’s solution, stained with hematoxylin–eosin, and observed under a light microscope at 400× magnification. Quantitative assessment focused on three types of nuclear abnormalities: pyknosis, karyorrhexis, and karyolysis. The Independent Samples t-test showed a significantly higher mean number of nuclear abnormalities in the exposed group than in the control group (12.47 ± 3.15 vs. 4.86 ± 1.92 cells/field; p < 0.001). Pyknosis was the most frequent alteration (58.3%), followed by karyorrhexis (26.7%) and karyolysis (15.0%). All procedures were approved by the institutional ethics committee. In conclusion, short-term exposure to 1800 MHz EMW from mobile devices under controlled conditions can induce measurable degenerative nuclear changes in oral epithelial cells, suggesting cellular susceptibility to non-ionizing radiation at the cytomorphological level.